HUBUNGAN MUTU PELAYANAN KESEHATAN DENGAN TINGKAT KEPUASAN PASIEN PESERTA BPJS DI UNIT RAWAT JALAN PENGOBATAN UMUM PUSKESMAS BANYUDONO II - Sarwoko .; Indra Rahmawati (STIKES Estu Utomo, 2024)
Background: Puskesmas is the spearhead of health services and development that needs attention in improving the quality of health services. Therefore, puskesmas are required to always provide professional and plenary services supported by increased knowledge, level of expertise and health facilities/facilities to provide satisfaction to the community. Objectives: to determine the relationship between the quality of puskesmas services and the level of satisfaction of BPJS participant patients in the Banyudono II Health Center Outpatient Unit, Boyolali Regency, in 2022. Method: Type of quantitative research with a cross sectional approach. The population in this study were all BPJS participant patients at the Banyudono II Health Center in the second week of October 2022, with the number of patients for 5 days an average visit (each week) of 97 patients. Sampling using the Slovin formula obtained a sample of 50 samples. Result: The results of statistical tests with the Spearman Rank Correlation test were obtained Sig. (2-tailed) p value 0.036 (p <? 0.05) the correlation coefficient value of the two variables is 0.298. Conclusion: From these results it can be concluded that Ha is accepted and Ho is rejected, meaning that there is a relationship between the quality of health services and the level of satisfaction of BPJS participant patients in the General Medicine Outpatient Unit at the Banyudono II Health Center. The level of relationship between the two variables is weak and unidirectional, which means that the better the quality of health services, the better the level of satisfaction.